Relationship between Knowledge and Compliance with the Implementation of Health Protocols in the Area of Educational Institutions in SMA/SMK in the district of Noemuti - Yusfina Modesta Rua; Veronika Nitsae; Paskalis Malafu Usfinit (Jurnal Manajemen Kesehatan Indonesia, 2022)
ABSTRACT The implementation of the new normal is of course with the implementation of strict health protocols, including in the area of educational institutions.The purpose of this study was to determine the relationship between knowledge and compliance in the implementation of health protocols, especially in the education area.This study is an observational analytic study with a cross-sectional design. The sample in this study amounted to 283 respondents consisting of teachers, staff, and students.The results of the chi-square test with a level of significance = 0.05 obtained p-value (α) = 0.026 < from value = 0.05 so that it shows that there is a relationship between knowledge and the level of compliance of students and teachers in implementing the covid 19 health protocol.Students and teachers SMA in Noemuti Sub-district have a good perception of behavior and attitudes in carrying out the implementation of the covid 19 health protocol. Compliance with the covid 19 health protocol is carried out well because they know the benefits and risks obtained and are supported by adequate knowledge.